Incidence of venous thromboembolism in patients with non-Hodgkin lymphoma. Issue 143 (July 2016) - Sanfilippo, K.M.; Wang, T.F.; Gage, B.F.; Luo, S.; Riedell, P.; Carson, K.R.
Abstract: Introduction: Patients with non-Hodgkin lymphoma (NHL) have an increased risk of venous thromboembolism (VTE). Current risk-prediction models classify NHL as a single entity. We aimed to quantify the difference in VTE risk in follicular lymphoma (FL) versus diffuse large B cell lymphoma (DLBCL). Methods: Using a prospective cohort study, we identified 2730 patients (2037 DLBCL; 693 FL) within the Veteran's Administration Central Cancer Registry. A competing risk model assessed the association between VTE risk and histology in the first year after NHL diagnosis. We assessed the effect of additional risk factors for VTE in NHL. Results: In univariate analysis, DLBCL was associated with increased risk of VTE compared to FL in the first year after diagnosis; this association was no longer significant in adjusted analysis (adjusted hazard ratio (aHR) 1.52; 95% CI 0.97–2.40). Major risk factors for VTE included history of VTE before NHL diagnosis (aHR 4.73, p  ≤ 0.0001) and time period during chemotherapy administration (aHR 7.60, p  ≤ 0.0001). Additional risk factors included: stage III/IV disease ( p  = 0.02), BMI ≥ 30 ( p  = 0.02), B-symptoms ( p  = 0.02), and doxorubicin ( p  = 0.04). The cumulative incidence of VTE was highest in the period following diagnosis and decreased over time for both histologies. Conclusion: DLBCL is associated with increased risk of VTE compared to FL. This risk is markedly attenuated when adjusting for additional risk factors. The strongest predictors for development of VTE included: time period during chemotherapy administration (especially doxorubicin) and history of VTE. This knowledge can assist clinicians in identifying NHL patients at high risk for VTE. Highlights: Competing risk analysis is used to identify risks for venous thromboembolism in lymphoma. Diffuse large B-cell lymphoma is associated with increased risk of thrombosis. Time during chemotherapy and history of thrombosis are the strongest risks for thrombosis. Risk of venous thromboembolism is highest immediately following lymphoma diagnosis.